1987
DOI: 10.1002/jcu.1870150306
|View full text |Cite
|
Sign up to set email alerts
|

Improved sonographic visualization of choledocholithiasis

Abstract: Ultrasonographic diagnosis of gallstones in the distal part of extrahepatic duct is not easy. A number of new techniques have been used by the authors to improve the detection rate of these stones. They include filling the duodenum and gastric antrum with drinking water, scanning after a fatty meal, and changing the patient's position during scanning. Ultrasound successfully identified choledocholithiasis in 78 of 104 patients for a sensitivity of 75%. There were 26 false-negative cases. The chief causes of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(12 citation statements)
references
References 12 publications
0
11
1
Order By: Relevance
“…US has a sensitivity of 90% and a specificity of 20–80%. CT has a sensitivity of 85% and a specificity of 88% [10, 11, 12]. …”
Section: Discussionmentioning
confidence: 99%
“…US has a sensitivity of 90% and a specificity of 20–80%. CT has a sensitivity of 85% and a specificity of 88% [10, 11, 12]. …”
Section: Discussionmentioning
confidence: 99%
“…6 In literature older studies showed less sensitivity, accuracy in comparison to recent studies. 5,6,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] Our study also showed higher sensitivity and accuracy compare to older studies for choledocholithiasis. Introduction of newer ultrasound equipments with tissue harmonic imaging has attributed significantly for this difference.…”
Section: Measures Ofmentioning
confidence: 60%
“…and current sonographic visualization of ductal stones is reported to be approximately 75-80% (38,44,45). There are several pitfalls in sonographic detection of common duct stones.…”
Section: Biliary Diseasementioning
confidence: 96%